2020
DOI: 10.4028/www.scientific.net/jera.50.70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Soil Inclination on Natural Convection in Half-Elliptical Greenhouses

Abstract: A numerical study of the natural convection of laminar heat transfers in the stationary state in a half-elliptic inclined cavity, which represents a continuation of the work done, we studied the influence of the tilt of the cavity by varying the angle — entered 0 degrees, which corresponds to the horizontal cavity, up to 15 degrees. For each value of δ we varied the Rayleigh number from 2.13 103 to 106. The system of equations governing the problem solved numerically by the fluent calculation code based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…The presence of longitudinal and transverse slopes on the ground influences the air flow patterns since these slopes favor a behavior where air flows lose velocity once they enter the greenhouse and in turn the air flow pattern tends to be directed vertically towards the roof ventilation areas while moving in a counter-slope direction. This type of flow pattern had already been reported in the study developed by Taloub et al [55], who concluded that any type of slope on the floor of the greenhouse, no matter how small, destabilizes the horizontal airflow and promotes the generation of vertical airflows and recirculatory movement patterns with low velocity zones near the leeward vents.…”
Section: Qualitative and Quantitative Characteristics Of Airflow Patternssupporting
confidence: 72%
“…The presence of longitudinal and transverse slopes on the ground influences the air flow patterns since these slopes favor a behavior where air flows lose velocity once they enter the greenhouse and in turn the air flow pattern tends to be directed vertically towards the roof ventilation areas while moving in a counter-slope direction. This type of flow pattern had already been reported in the study developed by Taloub et al [55], who concluded that any type of slope on the floor of the greenhouse, no matter how small, destabilizes the horizontal airflow and promotes the generation of vertical airflows and recirculatory movement patterns with low velocity zones near the leeward vents.…”
Section: Qualitative and Quantitative Characteristics Of Airflow Patternssupporting
confidence: 72%
“…Simplified method 62 [19,32,[37][38][39]46,49,76,78,83,91,95,99,100,106,[108][109][110][111][113][114][115][116][120][121][122][123]126,129,131,133,136,[141][142][143][144][145][146][147][148][149]151,[153][154][155][156][159][160][161][163][164]…”
Section: Radiation Model Number Of Documents Referenceunclassified
“…By considering that the flow of incompressible fluid, with constant physical properties by using the framework of the approximation of Boussinesq, the problem was solved numerically by the computational code fluent for different Rayleigh numbers and the number of Prandtl set at 0.7. Taloub et al [19] investigated numerically the natural convection of stationary laminar heat transfers in a semi-elliptical inclined cavity. The thermosolutal convection in an inclined square enclosure has been studied by Hadidi et al [20] in this case; the square enclosure is partially filled by a porous medium.…”
Section: Introductionmentioning
confidence: 99%